Dynamic Load Balancing and Scalability Analysis of the Mandelbrot Set in a Multi-Threaded HPC Application - Etcheverria, Francisco Pegoraro; Matos, Rayan Raddatz de; Brumati, Kenichi; Schnorr, Lucas Mello (Anais Estendidos do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2025: Anais Estendidos do XXVI Simpósio em Sistemas Computacionais de Alto Desempenho, 2025)
This work investigates load balancing and scalability in High-Performance Computing (HPC) systems using the Mandelbrot Set as a benchmark. Due to its irregular and computationally intensive workload, the Mandelbrot Set is ideal for evaluating dynamic workload distribution strategies. We present a custom MPI-based implementation employing a client-server model with dynamic load balancing, where idle workers request new work from a coordinator. Our contributions include implementing this parallel application and a performance analysis highlighting load imbalance and system scalability. The main results indicate that the granularity factor significantly influences load balance, and its choice depends on the selected fractal region.